DISTORSI PEMAKNAAN LAFADZ SHAHIBU MAKS ANTARA PETUGAS PEMUNGUT PAJAK DAN PUNGUTAN LIAR - Ana Fadhilah (Nizham Jurnal Studi Keislaman, 2018)
The biggest source of income for the country in Indonesia comes from taxes. The tax function is vital for the success of the country's development. However, in its management, tax officials were very vulnerable to being involved in fraud cases which resulted in a decline in public confidence, leading to a discourse on tax boycott initiated by one of the religious activists (Islam). They assume that all absolute tax employees are rewarded for hell, based on the hadith narrated from Uqbah "Lā yadkhulu al-jannata Shahibu Maksin" which means "Not to enter the heaven of a Shahibu Maksin (Maks Collector)". The question is "is it true that the maks in this hadith implies absolute tax, as is their understanding?" Because of this, they also assume that if the collector (employee) is only rewarded with hell, indirectly the object collected (tax) is absolutely prohibited in Islam. Based on this background, this paper is discuss the root of the problem from the emergence of the tax boycott discourse, namely the essence of the meaning of Shahibu Maks in the hadith narrated by Uqbah. But in answering this problem, it is necessary to explain in advance about "is there another compulsory levy on Muslim property, other than zakat?" From these questions later various opinions from the Muslim Scholars (Ulama’) will emerge to form conclusions regarding tax legality in Islam.